Novel AgCl / BiOCl-diatomite S-type heterostructure and application thereof in photocatalytic degradation

Through the new AgCl/BiOCl@diatomaceous earth S-type heterostructure, the problem of low degradation efficiency of existing photocatalytic materials on organic pollutants is solved, and efficient removal of drug-active compounds that are difficult to biodegrade are achieved, and catalytic performance is improved. and application potential of materials.

CN119455989AActive Publication Date: 2025-02-18CHANGCHUN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410797267.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-20
Publication Date
2025-02-18
Estimated Expiration
2044-06-20

AI Technical Summary

Technical Problem

Existing photocatalytic materials are inefficient in degrading organic pollutants, especially in poor removal of pollutants in wastewater from drug-active compounds that are difficult to biodegrade, such as carbamazepine (CBZ) and fluoroquinolones antibiotics.

Method used

Using the new AgCl/BiOCl@diatomaceous earth S-type heterostructure, BiOCl molar superglass nanosheets are modified by silver chloride and loaded on alkali-treated diatomaceous earth to form a close-contact AgCl/BiOCl S-type heterostructure , improve catalytic performance.

Benefits of technology

The removal efficiency of various organic pollutants is significantly improved, including azo dyes and pharmaceutically active compounds, and the carrier separation and redox capacity are improved, and the material is simple to prepare and easy to operate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455989A_ABST
    Figure CN119455989A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a novel AgCl / BiOCl-diatomite S-type heterostructure, the material is prepared by a two-step method, BiOCl nanosheets are loaded on diatomite through simple electrostatic self-assembly, and then AgCl and diatomite are deposited in situ through a photochemical method, so that the specific surface area of the composite material can be increased, the recoverability can be enhanced, and the preparation method is simple and easy to implement. A novel S-type heterostructure can be formed between AgCl and BiOCl, the S-type heterostructure can retain the highest redox potential of photon-generated carriers in the composite material and has very high carrier separation capacity, and compared with pure BiOCl, the novel AgCl / BiOCl-coated diatomite S-type heterostructure has the advantage that the degradation capacity on rhodamine b, tetracycline, norfloxacin and levofloxacin is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a novel AgCl / BiOCl@diatomite S-type heterostructure and application thereof in photocatalytic degradation, belonging to the technical field of photocatalytic materials. Background Art

[0002] The serious impact of wastewater containing azo dyes and pharmaceutically active compounds on the ecosystem and the potential threat to human health have attracted global attention in recent decades. Since the mid-1990s, organic pharmaceutical wastewater containing antibiotics has become one of the focuses of attention. Among them, fluoroquinolone antibiotics containing quinolone core structures such as norfloxacin, levofloxacin, and ciprofloxacin have been widely used in animal husbandry, healthcare industry, and aquaculture to treat infectious diseases. Therefore, a large amount of wastewater containing fluoroquinolone antibiotics and their residual molecules is released into the environment, resulting in a series of unknown environmental effects and serious environmental pollution; Carbamazepine (CBZ) is a widely studied emerging pollutant with a stable structure and difficult biodegradability, which exists for a long time in the wild. In addition, the presence of CBZ in water bodies poses a major threat to human health and other natural organisms. However, it is difficult to remove CBZ with traditional wastewater treatment technology. Based on this, it is urgent to solve the problem of pharmaceutical and organic pollutants in wastewater. Many methods including biological treatment, physical adsorption, chemical adsorption, Fenton-like oxidation and other methods have been applied, but there are still some problems to be solved. Therefore, it is of great significance to develop an efficient and safe technology for removing organic pollutants from wastewater.

[0003] Photocatalytic oxidation technology has attracted widespread attention due to its efficient degradation of organic pollutants, and thus many types of photocatalysts have been reported. Recently, bismuth-based catalysts such as BiVO 4 (BVO), Bi 2 WO 6 , BiOCl has received more and more attention. Among them, layered BiOCl exhibits unique photocatalytic activity and stability. However, due to the small specific surface area, easy agglomeration, low recovery rate, wide energy band gap, high probability of electron and hole recombination of monomer BiOCl, it can only respond to ultraviolet light, which seriously limits its application in real life. Summary of the invention

[0004] The purpose of the present invention is to provide a novel AgCl / BiOCl@diatomite S-type heterostructure and its application in photocatalytic degradation in view of the shortcomings of existing photocatalytic materials in degrading organic pollutants.

[0005] The novel AgCl / BiOCl@diatomite S-type heterostructure described in the present invention includes BiOCl mole superlattice nanosheets modified with silver chloride, which are loaded on alkali-treated diatomite. The mole superlattice material BiOCl nanosheet is used as a carrier of AgCl, which has a higher (001) crystal plane exposure. According to the crystal structure of BiOCl, the terminal chlorine of the (001) plane is exposed the most, and the Ag ion can be anchored on the terminal chlorine. The BiOCl nanosheet structure can break the Bi-Cl bond briefly under visible light to form a metastable state, thereby promoting the formation of silver chloride, which will have a closer contact than the additional introduction of a chlorine source. After further characterization, its unique S-type heterojunction mechanism is proved to effectively improve the catalytic performance.

[0006] In an embodiment of the present invention, the preparation of a novel AgCl / BiOCl@diatomite S-type heterostructure is achieved by the following steps:

[0007] (1) Dispersing BiOCl nanosheets and alkali-treated diatomaceous earth in deionized water respectively;

[0008] (2) slowly dropping the diatomite suspension into the BiOCl nanosheet suspension, stirring for 12 hours, and centrifugally drying to obtain a BiOCl@diatomite composite material; wherein the mass of the alkali-treated diatomite accounts for (5-30) / 100 of the total mass of the total BiOCl nanosheets and the alkali-treated diatomite;

[0009] (3) Dispersing the BiOCl@diatomite composite material in water, adding silver nitrate, stirring evenly, and irradiating under visible light for 40 minutes; the mass ratio of the BiOCl@diatomite composite material to silver nitrate is 20:

[0010] (1~16.9);

[0011] (4) After centrifugal washing, the mixture was placed in a vacuum drying oven at 60°C to obtain an AgCl / BiOCl@diatomite S-type heterostructure.

[0012] Furthermore, the BiOCl nanosheets of the mole superlattice are obtained by the following steps:

[0013] (1.1.1) Disperse 9.6 ml of 20 wt% PDDA (400000-500000) aqueous solution in 160 ml of ethylene glycol, add 0.19404 g Bi(NO 3 ) 3 ·5H 2 O, magnetic stirring for 30 min;

[0014] (1.1.2) Place the mixed solution in a 200°C oil bath and reflux for 2 h;

[0015] (1.1.3) After the solution is cooled to room temperature, centrifuge it with a high-speed centrifuge, wash it with deionized water three times, and place it in a vacuum drying oven at 60°C for 12 hours to obtain BiOCl nanosheets.

[0016] Further, the alkali-treated diatomaceous earth is obtained by the following steps:

[0017] (1.2.1) Mix natural diatomaceous earth with 5% NaOH solution, with a liquid-to-solid mass ratio of 3:1;

[0018] (1.2.2) Oil bath at 95°C, stir and maintain for 90 minutes

[0019] (1.2.3) After cooling to room temperature, rinse with a large amount of distilled water until neutral, and vacuum dry at 60°C for 6 hours to obtain alkali-treated diatomaceous earth.

[0020] Preferably, the mass of the alkali-treated diatomaceous earth accounts for 10% of the total mass of the BiOCl nanosheets and the alkali-treated diatomaceous earth.

[0021] Preferably, the mass ratio of the BiOCl@diatomite composite material to silver nitrate is 20:4.5.

[0022] The present invention also relates to the application of the novel AgCl / BiOCl@diatomite S-type heterostructure in photocatalytic degradation of azo dyes and pharmaceutically active compounds. The dyes include but are not limited to rhodamine B, and the pharmaceutically active compounds include but are not limited to tetracycline, levofloxacin, carbamazepine, and norfloxacin.

[0023] The beneficial effects of the present invention are:

[0024] (1) Different from the previous method of adding chlorine source, we used the terminal chlorine plates on the structure of BiOCl molar superlattice nanosheets as the chlorine source to prepare AgCl in situ, forming a close contact between AgCl and BiOCl, forming a new S-type heterostructure with a unique charge transfer mechanism, high carrier separation ability and high redox ability, which significantly improved the effective removal of various organic pollutants.

[0025] (2) The present invention creatively utilizes the characteristics of BiOCl molar superlattice nanosheets to construct a closely contacted AgCl / BiOCl S-type heterostructure, and the method is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1They are the morphology and structure diagrams of BiOCl nanosheets, alkali-treated diatomite, BiOCl@diatomite composite material (J-10), and AgCl / BiOCl@diatomite S-type heterostructure (J-10-2), respectively. Figure a is an X-ray diffraction analysis diagram of the initial material and the composite material, and Figures b, c, and d are scanning electron microscope images of alkali-treated diatomite, BiOCl nanosheets, and the preferred AgCl / BiOCl@diatomite S-type heterostructure (J-10-2), respectively; Figure e is a TEM image of the BiOCl nanosheet, which shows that it is a molar superlattice structure;

[0027] Figure 2 Zeta potential diagram of natural diatomite, alkali-treated diatomite, and BiOCl nanosheets, used to characterize surface electrical properties.

[0028] Figure 3 These are the nitrogen adsorption-desorption curves of original diatomite, alkali-treated diatomite, BiOCl nanosheets, and BiOCl@diatomite composite material (J-10) and the corresponding pore size distribution data.

[0029] Figure 4 UV-visible diffuse reflectance spectra of BiOCl nanosheets, BiOCl@diatomite composites and AgCl / BiOCl@diatomite S-type heterostructures (J-10-2).

[0030] Figure 5 a, b are the electrochemical impedance spectroscopy and photocurrent tests of BiOCl and AgCl / BiOCl@diatomite S-type heterostructure (J-10-2), respectively.

[0031] Figure 6 a and b are the valence band spectra of AgCl and BiOCl, respectively, which are used to determine their band structures.

[0032] Figure 7 It is the x-ray photoelectron spectrum of BiOCl and the in situ x-ray photoelectron spectrum of AgCl / BiOCl@diatomite S-type heterostructure (J-10-2). Where a is the Bi of pure BiOCl, AgCl / BiOCl@diatomite S-type heterostructure (J-10-2) in the dark, and AgCl / BiOCl@diatomite S-type heterostructure (J-10-2) under illumination. 4f Spectrum, b is the corresponding O 1S Spectrum, c is the corresponding Cl 2p Spectra, d is the Ag of AgCl / BiOCl@diatomite S-type heterostructure (J-10-2) under dark and light conditions 3d Spectrum.

[0033] Figure 8 It is the UV photoelectron spectrum of BiOCl and AgCl.

[0034] Fig. 9 a, b, c, d, e, f, g are the catalytic properties of BiOCl nanosheets, BiOCl@diatomite, and AgCl / BiOCl@diatomite S-type heterostructures, and the test diagrams of catalytic stability. Among them, a is the degradation effect diagram of rhodamine b after BiOCl and diatomite in different proportions, and b is the degradation effect diagram of rhodamine b by AgCl / BiOCl@diatomite S-type heterostructures. c, d, e, and f are the catalytic effect diagrams of BiOCl nanosheets, BiOCl@diatomite, and AgCl / BiOCl@diatomite S-type heterostructures for the degradation of tetracycline, levofloxacin, carbamazepine, and norfloxacin, respectively. Figure g is the cyclic stability test diagram of the degradation of rhodamine b. DETAILED DESCRIPTION

[0035] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0036] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0037] In the following examples, the photocatalytic test method is as follows: Rhodamine B solution (10 mg / L), carbamazepine solution (20 mg / L), norfloxacin (10 mg / L), tetracycline (10 mg / L), and levofloxacin (15 mg / L) are used as target degradation products, 50 mL of each solution is put into a glass reactor, the outer layer of the container is kept at a constant temperature using condensed water, and a 300W xenon lamp (filter>400nm) visible light is used as the light source, and 15 mg of the sample is added. Dark treatment for 30 minutes to reach adsorption and desorption equilibrium, and samples are taken once every 20, 40, 60, 80, and 100 minutes, respectively. The samples are centrifuged at 10000 r / min for 10 minutes, and the supernatant is taken. The pollutant concentration (C / C) is measured using a UV-8500 ultraviolet-visible spectrophotometer (UV-Vis). 0 ) are plotted.

[0038] Example 1

[0039] This embodiment prepares the AgCl / BiOCl@diatomite S-type heterostructure, which specifically includes the following steps:

[0040] 1. Preparation of alkali-treated diatomaceous earth

[0041] (1.1) Pour 1 g of natural diatomaceous earth into a 250 ml two-necked flask, then weigh 3 g of 5% NaOH solution using a balance and drop it into the two-necked flask using a rubber-tipped dropper, mix, and place in an oil bath at 95°C with stirring for 90 minutes.

[0042] (1.2) After cooling to room temperature, rinse with a large amount of distilled water until neutral, and vacuum dry at 60°C for 6 hours to obtain alkali-treated diatomaceous earth.

[0043] 2. Preparation of BiOCl nanosheets, specifically:

[0044] (2.1) Use a 100 ml graduated cylinder to measure 160 ml of ethylene glycol solution, then pour it into a 250 ml double-necked flask and stir. Use a pipette to take 9.6 ml of a 20 wt% aqueous solution of PDDA (molecular weight 400.000-500.000), drop it into the above double-necked flask, continue to stir vigorously, and then add Bi(NO 3 ) 3 ·5H 2 O, magnetic stirring for 30 min;

[0045] (2.2) The mixed solution was transferred to an oil bath at 200 °C and heated under reflux for 2 h.

[0046] (2.3) After the mixed solution is cooled to room temperature, centrifuge, wash and dry it. Centrifuge it in a high-speed centrifuge for 15 minutes, wash it with deionized water three times, and dry it in a vacuum drying oven at 60°C for 4 hours.

[0047] 3. Preparation of BiOCl Nanosheets Supported on Alkali-treated Diatomaceous Earth

[0048] (3.1) 1.2, 2.4, 4.8, 7.2, and 9.6 mg of alkali-treated diatomaceous earth were dispersed in 30 ml of deionized water by ultrasonic treatment for one hour, and 22.8, 21.6, 19.2, 16.8, and 14.4 mg of BiOCl nanosheets were dispersed in 20 ml of deionized water by ultrasonic treatment for 10 minutes, respectively;

[0049] (3.2) At room temperature and a stirring speed of 450 rpm, the BiOCl nanosheet solution was slowly added dropwise to the alkali-treated diatomite solution. Stirring was continued for 12 h; the resulting catalysts were labeled as J-5 (1.2 mg alkali-treated diatomite + 22.8 mg BiOCl nanosheets), J-10 (2.4 mg alkali-treated diatomite + 21.6 mg BiOCl nanosheets), J-20 (4.8 mg alkali-treated diatomite + 19.2 mg BiOCl nanosheets), J-30 (7.2 mg alkali-treated diatomite + 16.8 mg BiOCl nanosheets), and J-40 (9.6 mg alkali-treated diatomite + 14.4 mg BiOCl nanosheets);

[0050] (3.3) The final solution was centrifuged, washed and dried. Centrifuge for 5 minutes in a high-speed centrifuge, wash once with deionized water, and dry in a vacuum drying oven at 60°C for 4 hours.

[0051] Fig. 9 a is the optimal ratio of BiOCl@diatomite composite materials in the early exploration. First, through the photodegradation experiment of diatomite treated with soda ash, we found that the alkali-treated diatomite was mainly physical adsorption, without obvious photodegradation performance, and it can also be seen that the adsorption-desorption equilibrium has been reached in 30 minutes. Secondly, we conducted a 100-minute photodegradation test with different diatomite input ratios. Through the degradation efficiency in the first sixty minutes, we can see that with the amount of alkali-treated diatomite input, the degradation performance shows a trend of first increasing and then decreasing. J-10 has the highest degradation efficiency. The main reason is that after the appropriate proportion of diatomite is added to the BiOCl nanosheets, its specific surface area is increased, but the diatomite itself has almost no degradation performance, and excessive diatomite will hinder the light absorption of the BiOCl nanosheets, thereby reducing the degradation efficiency of the composite material.

[0052] 4. Preparation of AgCl / BiOCl@diatomite S-type heterostructure

[0053] (4.1) 20 mg of BiOCl@diatomite composite material J-10 was dispersed in 50 ml of water by ultrasonication for ten minutes.

[0054] (4.2) Add 1 mg, 4.5 mg and 16.9 mg of silver nitrate to the above solution, stir for ten minutes, and irradiate under a 300 W xenon lamp (wavelength greater than 400 nm) for 40 minutes. Mark them as J-10-1, J-10-2 and J-10-3 respectively.

[0055] (4.3) The final solution was centrifuged, washed and dried. Centrifuge for 5 minutes in a high-speed centrifuge, wash three times with deionized water, and dry in a vacuum drying oven at 60°C for 4 hours.

[0056] The test results of AgCl / BiOCl@diatomite S-type heterostructure are as follows Fig. 9 As shown in Figure b, when the initial input of silver nitrate is 4.5 mg (J-10-2), the degradation rate of rhodamine b is as high as 98% after continuous irradiation for 30 minutes (the catalytic effect of other pollutants is greatly improved, which are Fig. 9 cTetracycline, Fig. 9 dLevofloxacin, Fig. 9 eCarbamazepine, Fig. 9f norfloxacin), compared with the J-10 composite catalyst, the degradation effect of J-10-2 is greatly improved compared with the original BiOCl nanosheets. The reason is that AgCl and BiOCl form a new S-type heterojunction, which has a unique charge transfer mechanism, resulting in faster carrier separation ability and stronger carrier redox ability, further improving the photocatalytic activity.

[0057] Fig. 9 g is the reaction diagram of the degradation of Rhodamine B by J-10-2 after repeated use for three times. It can be seen that the degradation of Rhodamine B can be completed within 40 minutes after repeated use for three times. It can be seen that the composite material has excellent stability and recyclability.

[0058] from Figure 7 a X-ray photoelectron spectroscopy shows that compared with the original BiOCl, the Bi 4f, O 1s, and Cl 2p orbital binding energies of the AgCl / BiOCl@diatomite S-type heterostructure (J-10-2) have a certain degree of shift, which represents the change in electron cloud density caused by the close contact between AgCl and BiOCl. Compared with the original BiOCl, the two orbitals of Bi in the AgCl / BiOCl@diatomite S-type heterostructure (J-10-2) are shifted to high binding energy, but after illumination, they are shifted to low binding energy positions compared to the dark, and Figure 7 The same phenomenon is also found in b and c, but the 3d 3 / 2 3d 5 / 2 In contrast, the dark part moves toward the high binding energy. These four pictures combined prove that the prepared AgCl / BiOCl@diatomite composite material (J-10-2) conforms to the new S-type heterostructure, that is, when BiOCl is compounded with AgCl, the work function of BiOCl is smaller than that of AgCl ( Figure 8 ), the electrons of BiOCl will spontaneously flow to AgCl, so the binding energies of the two orbitals of Bi and O are both shifted to the high binding energy. Further, the band bending is caused at the contact interface. Due to the high electron density on AgCl and the high hole density on BiOCl, a strong built-in electric field is formed at the contact interface, driving the separation and migration of photogenerated carriers. When illuminated, due to the built-in electric field, the electrons flow to BiOCl, which is shown in the figure as the binding energies of the two orbitals of Bi and O are both shifted to the low binding energy after illumination, while the two orbitals of Ag are both shifted to the high binding energy. 7b O in the composite material 1s A new peak appeared at 531.8 in the spectrum, which was considered to be the Si-O bond, which also proved that the composite material was successfully prepared.

[0059] from Figure 8 The work function can be calculated according to the formula Φ = hv + E cutoff-E F (where hv = 21.22 eV), it can be seen that the work function of BiOCl is smaller than that of AgCl. Combined with the above X-ray photoelectron spectroscopy, it is proved that the AgCl / BiOCl@diatomite S-type heterostructure is successfully prepared.

[0060] from Figure 1 a X-ray diffraction pattern, 1c SEM image of BiOCl nanosheets, 1e TEM image of BiOCl. Comprehensive analysis shows that the BiOCl nanosheets we synthesized grow along a single axis and have moiré fringes, successfully forming a moiré superlattice structure. Figure 1 In b, we can see that the pore and disc structures of diatomite treated with alkali are well maintained. Figure 1 In c, we can see that BiOCl nanosheets are loaded onto the surface of diatomite. Furthermore, silver chloride nanoparticles are also loaded onto the BiOCl / alkali-treated diatomite composite material. The XRD diffraction peaks of the J-10 and J-10-2 composite materials remain basically unchanged. The J-10-2 composite material only has an additional characteristic peak of silver chloride, and does not damage the original crystal structure, proving that the material synthesis was successful.

[0061] from Figure 2 It can be seen from the Zeta potential that BiOCl nanosheets are positively charged, and the alkali-treated diatomaceous earth is more negatively charged than the natural diatomaceous earth, which proves the theoretical feasibility of electrostatic self-assembly.

[0062] from Figure 3 It can be seen that the specific surface area and average pore size of diatomite after alkali treatment are greatly improved, and the specific surface area and pore size of the preferred BiOCl@diatomite composite material (J-10) are further improved than those of BiOCl nanosheets.

[0063] from Figure 4 From the UV-visible diffuse reflectance spectrum, it can be seen that the AgCl / BiOCl@diatomite S-type heterostructure has a narrower band gap and a wider light absorption range than the initial BiOCl nanosheets.

[0064] from Figure 5 a Electrochemical impedance spectroscopy and 5b photocurrent show that the AgCl / BiOCl@diatomite S-type heterostructure has a higher photocurrent and a smaller carrier transfer resistance, which indicates that it has a better carrier separation ability.

[0065] from Figure 6 The valence band spectrum combined with the previous UV-visible diffuse reflectance spectrum can be used to calculate that the positions of the valence band and conduction band of AgCl are 2 and -0.96 respectively; the positions of the valence band and conduction band of BiOCl are 1.1 and -1.5 respectively. This proves that the valence band and conduction band structures of AgCl and BiOCl are relatively matched, meeting the requirements of S-type heterojunction.

[0066] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.

Claims

1. A novel AgCl / BiOCl@diatomite S-type heterostructure, characterized in that: Prepared by the following steps: (1) Dispersing BiOCl nanosheets and alkali-treated diatomite in deionized water respectively; adding the alkali-treated diatomite suspension dropwise to the BiOCl nanosheet suspension, stirring for 12 hours, and centrifugally drying to obtain a BiOCl@diatomite composite material; wherein the mass of the alkali-treated diatomite accounts for (5-30) / 100 of the total mass of the BiOCl nanosheets and the alkali-treated diatomite; (2) Dispersing the BiOCl@diatomite composite material in water, adding silver nitrate, stirring evenly, and irradiating under visible light for 40 minutes; the mass ratio of the BiOCl@diatomite composite material to silver nitrate is 20: (1~16.9); (3) After centrifugal washing, the mixture was placed in a vacuum drying oven at 60°C to obtain an AgCl / BiOCl@diatomite S-type heterostructure.

2. The AgCl / BiOCl@diatomite S-type heterostructure according to claim 1, characterized in that: The BiOCl nanosheets in step 1 are prepared by the following steps: (1.1) Disperse 9.6 ml of 20 wt% PDDA aqueous solution in 160 ml of ethylene glycol, add 0.19404 g Bi(NO3)3·5H2O, and stir magnetically for 30 min; (1.2) Place the mixed solution in a 200°C oil bath and heat under reflux for 2 h; (1.3) After the solution is cooled to room temperature, centrifuge it, wash it with deionized water for three times, and place it in a vacuum drying oven at 60°C for 12 hours to obtain molar superlattice BiOCl nanosheets.

3. The AgCl / BiOCl@diatomite S-type heterostructure according to claim 1, characterized in that: The alkali-treated diatomaceous earth in step 1 is prepared by the following steps: (2.1) Mix natural diatomaceous earth with 5% NaOH solution at a liquid-to-solid ratio of 3:1; (2.2) Oil bath at 95°C, stir and maintain for 90 minutes; (2.3) After cooling to room temperature, rinse with water until neutral, and dry in vacuo at 60°C to obtain alkali-treated diatomaceous earth.

4. The AgCl / BiOCl@diatomite S-type heterostructure according to claim 1, characterized in that: The mass of alkali-treated diatomite accounts for 10% of the total mass of BiOCl nanosheets and alkali-treated diatomite.

5. The AgCl / BiOCl@diatomite S-type heterostructure according to claim 1, characterized in that: The mass ratio of BiOCl@diatomite composite material to silver nitrate is 20:4.

5.

6. Use of the novel AgCl / BiOCl@diatomite S-type heterostructure as claimed in claim 1 in photocatalytic degradation of azo dyes and pharmaceutically active compounds.

7. The use according to claim 6, characterized in that: The dye includes but is not limited to rhodamine B, and the pharmaceutically active compound includes but is not limited to tetracycline, levofloxacin, carbamazepine, and norfloxacin.

Citation Information

Patent Citations

  • AgCl / BiOCl photocatalyst with tubular AgCl structure

    CN108097273A

  • Synthesis and application of highly dispersed BiOCl / diatomite photocatalyst

    CN109331845A